2020
DOI: 10.2147/dddt.s258024
|View full text |Cite
|
Sign up to set email alerts
|

<p>Osteogenic Effect of tsRNA-10277-Loaded Exosome Derived from Bone Mesenchymal Stem Cells on Steroid-Induced Osteonecrosis of the Femoral Head</p>

Abstract: Purpose Steroids are known to inhibit osteogenic differentiation and subsequent bone formation in bone mesenchymal stem cells (BMSCs). However, little is known about the role of BMSC exosomes (Exos) and tRNA-derived small RNAs (tsRNAs) in steroid-induced osteonecrosis of the femoral head (SONFH). The objective of this study was to characterize the tsRNA expression profiles of plasma Exos collected from SONFH patients and healthy individuals using small RNA sequencing and further explore the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Another degenerative bone disease where exosomal tRNAs showed significant changes in levels was identified in patients suffering from steroid-induced osteonecrosis of the femoral head (SONFH). Fang et al [ 61 ] compared the expression profile of exosomal tsRNA in a small number ( n = 10) of SONFH patients with healthy controls, and further sought to characterise the effect bone marrow-derived stem cell (BMSC) exosomes had on the pathogenesis of SONFH. The authors found three exosomal tsRNAs expressed at significantly lower levels in SONFH patients, validated by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Another degenerative bone disease where exosomal tRNAs showed significant changes in levels was identified in patients suffering from steroid-induced osteonecrosis of the femoral head (SONFH). Fang et al [ 61 ] compared the expression profile of exosomal tsRNA in a small number ( n = 10) of SONFH patients with healthy controls, and further sought to characterise the effect bone marrow-derived stem cell (BMSC) exosomes had on the pathogenesis of SONFH. The authors found three exosomal tsRNAs expressed at significantly lower levels in SONFH patients, validated by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…This potential link between secretion of exosomes containing these two RNAs by ESCC cells and increased amount of them in salivary exosomes from ESCC patients suggested that their amounts in salivary exosomes might have diagnostic and/or prognostic value. Although tsRNAs in exosomes were investigated in some published studies [ 16 , 35 37 ], this is the first report of salivary exosomal tsRNA as a disease biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing this strategy, tRNA derived small non-coding RNA-10277 i.e., tsRNA-10277 was loaded into BMSC derived exosomes. These tsRNA-10277 enriched exosomes were shown to enhance osteogenic differentiation of recipient BMSCs [61]. Overall, from the available literature it appears that tRFs are a biproduct of cellular metabolism, expelled into exosomes, which have distal gene regulatory effect.…”
Section: Trnamentioning
confidence: 97%
“…When a particular nucleic acid is overexpressed in cell either from a plasmid or due to change in cellular microenvironment, the excess nucleic acid gets routed in MVB and gets exported as exosomal cargo. To exemplify, delivery of exosomal tsRNA-10277 [61], circRNA NRIP [84] or mRNA [98] fit in this model. Induction of double stranded breaks in genomic DNA yields excess DNA fragments which gets packaged in the exosome [106].…”
Section: Cellular Abundance Induced Packaging Modelmentioning
confidence: 99%